In Uzbekistan, the Possibility of Limited POPULATION of the Architecture of the Environment for the Organization - Isakova Mukaddas Badirovna (Journal of Learning on History and Social Sciences, 2024)
in this article in uzbekistan for persons with disabilities "convenient architectural environment" of the organization, the main problems are discussed. These issues and analysis, "environment" to improve the quality of the design and construction of elements to give you recommendations on fail to keepadi.